Ocena pomiarów kąta zeza za pomocą synoptoforu i pryzmatycznego testu naprzemiennego zasłaniania - Nowakowska, Olimpia; Broniarczyk-Loba, Anna (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Ophthalmologists specialised in strabology are faced with the dilemma which method of strabismus measurement gives the most reliable results. The correct measurement result is of a primary importance when a squint surgery is to be performed. The aim of this study was to compare two methods of the angle measurement: synoptofore testing and PCT. The study consisted of 200 squint angle measurements including PCT for distance and near as well as objective strabismus angle measurement with synoptofore. One hundred measurements of ET and one hundred measurements of XT were done. Significant differences between results of synoptofore and PCT method were noticed for patients both type of strabismus. Measurement performed with synoptophore shows the increase of convergence in most cases.